1999
DOI: 10.1073/pnas.96.23.13023
|View full text |Cite
|
Sign up to set email alerts
|

A model-based approach for assessingin vivocombination therapy interactions

Abstract: We present an approach for evaluating the efficacy of combination antitumor agent schedules that accounts for order and timing of drug administration. Our model-based approach compares in vivo tumor volume data over a time course and offers a quantitative definition for additivity of drug effects, relative to which synergism and antagonism are interpreted. We begin by fitting data from individual mice receiving at most one drug to a differential equation tumor growth/drug effect model and combine individual pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…4 Up to date, it has been reported that the antibodies against ERGF or HER2 can potentiate the DNA-damaging cytotoxic effects of chemotherapeutic agents. 56,57 CRM197 may enhance the same DNA-damaging cytotoxic anti-tumor effects of paclitaxel as anti-EGFR antibodies (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…4 Up to date, it has been reported that the antibodies against ERGF or HER2 can potentiate the DNA-damaging cytotoxic effects of chemotherapeutic agents. 56,57 CRM197 may enhance the same DNA-damaging cytotoxic anti-tumor effects of paclitaxel as anti-EGFR antibodies (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the evaluation of the most promising combinations of a new compound with other anticancer agents, including those already available on the market, is become a fundamental step in early drug development for obtaining a complete description of the compound characteristics [20]. For this purpose, ad-hoc in vitro and in vivo experiments, based on cell cultures and tumor-bearing animals, are routinely performed to assess if the combination has a synergistic, additive or antagonistic interaction (i.e., the effect of the combination is more/equal/less what would be as predicted from the knowledge of the monotherapies) [2, 7, 8, 11, 16]. One of the main objectives of screening experiments during the early drug development is to identify drug combinations that yield an enhanced pharmacological effect and to prioritize them according to their interaction intensity.…”
Section: Introductionmentioning
confidence: 99%
“…The function f is some feature of the curve, such as Peak = max r ( t ) or area under the curve . This concept of additivity has been previously used in the context of a specific model of tumor growth [ 19 ]. Extending this concept, a combination therapy is synergistic if , sub -additive if and antagonistic if .…”
Section: Methodsmentioning
confidence: 99%